A study on the development of a fear of competition scale for elite athletes - Park, S. H.; Ahn, H. (Research in Dance and Physical Activity, 2024)
This study was conducted with the purpose of developing a scale to measure the fear of competition that elite athletes feel before competition. Accordingly, data to verify construct validity were collected, results were calculated based on data analysis procedures, and the following conclusions were obtained. First, the fear of competition perceived by elite athletes was finalized to be 12 questions in four factors: burden of expectations from people around them, threat of injury in competition, concern about results such as failure, and loss of effort. Second, as a result of cross-validating the difference in fear of competition according to gender in the developed fear of competition scale, female athletes showed a higher level of fear than male athletes. Therefore, the fear of competition scale developed in this study was confirmed to be valid. Based on these research results, we discussed them from the perspective of prior research and field application.